Challenges to conducting a 12-month longitudinal qualitative study on Chinese primary care physicians (INTERNATIONAL JOURNAL OF RESEARCH IN EDUCATION METHODOLOGY, 2015)
Background: Qualitative approach is commonly adopted in medical education research. However, it is difficult to conduct research studies on primary care physicians (PCPs). Conducting longitudinal qualitative studies is even more challenging. No studies on Chinese PCPs in this area are identified. Methods: We invited 14 Chinese PCPs to participate in a 12-month longitudinal qualitative study which explored their continuing professional learning experiences and viewpoints. They reported their learning activities by questionnaires in which the findings served as a guide for subsequent interviews. Each of them took part in four individual interviews spanning 12 months. We detailed the conduction process and challenges in a research diary and analyzed these data by thematic content analysis. Results: The major challenges were identification and recruitment of eligible PCPs. We tackled these challenges with the assistance of our professional networks and opinion leaders. We offered the participants an intellectual incentive by designing our study relevant to their profession. Flexibility and convenience of data collection could minimize the heavy burden on them. Conclusions: With appropriate recruitment strategies and planning of the research methods, researchers can successfully conduct longitudinal qualitative studies on Chinese PCPs about their learning experiences.